2017
DOI: 10.1177/0300985817705172
|View full text |Cite
|
Sign up to set email alerts
|

Hypervirulent Klebsiella pneumoniae in California Sea Lions (Zalophus californianus): Pathologic Findings in Natural Infections

Abstract: Tissues of stranded California sea lions ( Zalophus californianus) naturally infected with a hyperviruluent strain of Klebsiella pneumoniae were examined by histopathology and immunohistochemistry against the K. pneumoniae K2 capsular antigen. In 7 of 8 animals, there was severe purulent bronchopneumonia, sometimes complicated by fibrinonecrotizing pleuritis with pyothorax. In affected areas of lung, large numbers of degenerate neutrophils and macrophages were admixed with rare large extracellular and intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The causal isolate was later identified as a hypermucoviscous phenotype (Roe et al, 2015), but appears not to be of human origin (Castinel et al, 2007). A similar isolate has also been reported in CSLs (Jang et al, 2010;Seguel et al, 2017a). The clinical presentation of hypermucoviscous K. pneumoniae varies somewhat between host species.…”
Section: Bacteriamentioning
confidence: 97%
See 1 more Smart Citation
“…The causal isolate was later identified as a hypermucoviscous phenotype (Roe et al, 2015), but appears not to be of human origin (Castinel et al, 2007). A similar isolate has also been reported in CSLs (Jang et al, 2010;Seguel et al, 2017a). The clinical presentation of hypermucoviscous K. pneumoniae varies somewhat between host species.…”
Section: Bacteriamentioning
confidence: 97%
“…Disease has not been reported in juveniles or adults. Pleuritis, pyothorax, pneumonia, and abscesses are the most frequent lesions in CSLs and appear to occur in all ages (Jang et al, 2010;Seguel et al, 2017a), and septicemia and meningoencephalitis have recently been identified. Additionally, Spraker et al (2007) describe a syndrome in CSLs on San Miguel Island, Several different Mycoplasma spp.…”
Section: Bacteriamentioning
confidence: 99%
“…However, hypervirulent strains have been reported to cause various severe infections in immunocompetent and young healthy individuals [ 13 ]. hvKp has been implicated in causing pulmonary lesions in animals, such as suppurative bronchopneumonia in sheep [ 14 ], purulent bronchopneumonia in sea lions [ 15 , 16 ], pneumonia in Boer goats [ 17 ], and pneumonia and bacteremia in non-human primates [ 18 ]. On the other hand, hvKp infection in cattle is widely recognized as the causative agent of mastitis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of the isolates were also resistant to cephalothin, ampicillin, and moxifloxacin. It must be noted that the isolated Klebsiella spp., and Escherichia spp., bacterial species often reported as pathogenic to cetaceans, were resistant to erythromycin [71][72]. Similarly, high resistance to erythromycin, cephalothin, and ampicillin of E.…”
Section: Antibiotic Resistant Bacteria From Stranded Cetaceansmentioning
confidence: 99%